Chapter 24 Working Together in the Aftermath of an Unforeseen Event - Halvorsen, Kjersti (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The frame of this chapter is how clinicians and leaders employed in psychiatric departments in hospitals experience and cope with patients who commit suicide while undergoing treatment. The major focus is the phenomenon which in the Bow-tie model is called "stabilization". To explore this phenomenon in an empirical analysis, two concepts of samhandling are introduced, these being coordination and cooperation. These two concepts are used in an interpretation of what eight leaders and clinicians report on how they handle working together after a patient during treatment in a psychiatric hospital has unexpectedly committed suicide. The findings are that leaders and clinicians have different views on what stabilization is. Stabilization to the leaders seems to be something they can handle by using mandatory organizational procedures of coordination. To the clinicians (psychologists and psychiatrists) however, stabilization is less straightforward. Professional stabilization is, to them, more important than organizational stabilization, and it requires another form of interaction - namely, cooperation. Cooperation is, in its simplest and purest form, a symmetrical way of working together, based on equality in competence and an unforced relation between the parties. For the purpose of professional stabilization, this is the form of interaction preferred by the clinicians. However, these findings are tentative and more research is needed to elaborate why leaders and clinicians respond as they do after a patient suicide."